Development of grammar, vocabulary, and pragmatics in an additional language: insights from Spanish learner corpus research. (3rd July 2022) - Gudmestad, Aarnes
ABSTRACT: The current article offers an overview of scholarship on additional-language (e.g., second-language, heritage-language) users of Spanish that has been carried out using learner corpora in the last decade. I focus the review of Spanish learner corpus research on investigations that have examined grammar (e.g., fluency, grammatical gender), vocabulary (e.g., lexical diversity), and pragmatics (e.g., discourse markers), and I highlight the contributions that this body of work has made to the understanding of the use and development of additional-language Spanish. I also discuss the pedagogical applications that this line of inquiry may have. I conclude by identifying specific avenues for future work pertaining to research on additional-language learning and the development of new corpora.